A multi-spark electrohydraulic shock wave generator with adjustable pressure field distribution and beam steering capability - Sankin, Georgy N.; Fang, Zheng; Gu, Juanjuan; Jing, Yun; Zhong, Pei (Frontiers in Urology, 2023)
Background and objective All clinical shock wave lithotripters produce an axisymmetric acoustic field without accounting for the anatomic features of the kidney or respiratory motion of the patient. This work presents a steerable and adjustable focusing electrohydraulic (SAFE) shock wave generator design with variable beam size and shape. Materials and methods 90 electrohydraulic transducers are mounted concentrically on a spherical basin with adjustable connection to individual transducers. Each transducer consists of 45 3D-printed titanium microelectrodes embedded in epoxy with a tip diameter of 0.3 mm. All the transducers are arranged in 5 concentric rings and sub-divided into 6 sectors. Results By changing the connections of individual transducers, the focused pressure field produced by the transducer array can be either axisymmetric with a -6 dB focal width of 14.8 mm in diameter, or non-axisymmetric with a long axis of 22.7 mm and a short axis of 15.1 mm. The elongated beam produces a peak positive pressure of 33.7 ± 4.1 MPa and comminution efficiency of 42.2 ± 3.5%, compared to 36.2 ± 0.7 MPa and 28.6 ± 6.1% for axisymmetric beam after 150 pulses at 20 kV. Conclusions We have demonstrated that the SAFE shock wave generator can produce an elongated non-axisymmetric pressure field with higher stone comminution efficiency. The SAFE shock wave generator may provide a flexible and versatile design to achieve accurate, stable, and safe lithotripsy for kidney stone treatment.